FRI0488 Psoriatic arthritis in the united states: increasing all-cause hospitalizations 1993–2014. (15th June 2017) - Singh, G; Moise, C; Mithal, A; Ionescu, R; Mithal, A
Abstract : Background: Psoriatic arthritis (PsA) is a rare disease, with an estimated prevalence of 0.02 – 0.42% in Europe and US (1). PsA is often regarded as a mild disease, but recent data suggest an increase in comorbidities and mortality, possibly related to systemic inflammation (1). Objectives: To study all-cause hospitalizations in patients with PsA in the United States (US) from 1993 to 2014. Methods: The Nationwide Inpatient Sample (NIS) is a stratified random sample of all US community hospitals. It is the only US national hospital database with information on all patients, regardless of payer, including persons covered by Medicare, Medicaid, private insurance, and the uninsured. We examined all inpatient hospitalizations in NIS from 1993 to 2014 with a primary or secondary diagnosis of PsA, and compared them to total all-cause US hospitalizations during the same period. US population estimates and projections for the resident US population were obtained from the US Census Bureau. Results: There were 789.8 million all-cause hospitalizations in 6.4 billion person-years of observation from 1993 to 2014 (123.4 hospitalizations per 1, 000 person-years). During this time-period, 332, 496 hospitalizations occurred in patients with PsA (5.2 per 100, 000 person-years). All-cause US hospitalizations increased from 33.7 million in 1993 to 35.4 million in 2014, an increase of 4.8% over 22 years (Figure, dotted blue line). All-cause hospitalizations in PsA patients have increased from 6, 866 in 1993 (2.6 per 100, 000 person-year) to 33, 875 in 2014 (10.6 per 100, 000 person-years, a dramatic increase of over 393% (p<0.0001, Figure solid red line). In 2014, hospitalizations in PsA patients accounted for 163, 630 hospital days at a total national cost of over US$1.66 billion. Conclusions: All-cause hospitalizations in patients with PsA in the US have significantly increased by 393% in the last 22 years, almost 80-fold of the 4.8% increase in US population all-cause hospitalization rate in the same time-period. This calls for an increase need for identification and management of serious co-morbid conditions in patients with PsA. References: J Gelfand, D Gladman et al. Epidemiology of Psoriatic Arthritis in the Population of the United States. J Am Acad Dermatology, vol 53, p 573–577. Disclosure of Interest: None declared